Предмет: Математика,
автор: geralove
Реши уравнение: 3(2x – 3) – 5(х + 4) = 2(3x
+ 5) + 5х.
Ответ:
Ответы
Автор ответа:
3
Ответ:
3(2х-3)-5(х+4)=2(3х+5)+5х
6х-9-5х-20=6х+10+5х
6х-5х-6х-5х=10+20+9
-10х=39
Х= - 3,9
geralove:
спасибо большое
Автор ответа:
0
Ответ:-3.9
Пошаговое объяснение:
3(2х-3)-5(х+4)=2(3х+5)+5х
6х-9-5х-20=6х+10+5х
х-29=11х+10
х-11х=10+29
-10х=39
х=39:(-10)
х=-3.9
Похожие вопросы
Предмет: Русский язык,
автор: никита3127
Предмет: Русский язык,
автор: sum2001
Предмет: Английский язык,
автор: 4514452121
Предмет: Математика,
автор: EnergyLon
Предмет: Математика,
автор: анна124Fox